Observing Conflict Escalation in World Society : Ukraine's Maidan and Mali's Breakup - Bösch, Richard (2023)
How do conflicts escalate? This is one of the major questions in conflict research. To offer further answers, Richard Bösch follows a tripartite agenda: First, he develops a constructivist methodology for the study of conflict escalation embedded in a Luhmannian systems theoretical world society perspective. Bösch argues that conflicts can be observed as social systems and he looks at the process of conflict escalation by analysing communication. Second, this analysis offers two case studies: the Maidan protests in Ukraine 2013-2014 and Mali's crisis 2010-2012. Third, it gives insights on how systems theoretical research can be beneficial for Peace and Conflict Studies.